Potential for sublethal insecticide exposure to impact vector competence of Aedes albopictus (Diptera: Culicidae) for dengue and Zika viruses - Richards, Stephanie L (Res Rep Trop Med, 2017)
Chikungunya, dengue, and Zika viruses (CHIKV, family Togaviridae, genus Alphavirus; DENV and ZIKV, family Flaviviridae, genus Flavivirus) are arboviruses that cause human epidemics. Due to the lack of vaccines for many mosquito-borne diseases, there is a need for mosquito control. In the US and other regions, residual barrier insecticide sprays are applied to foliage where female mosquitoes rest and/or sugar feed between blood meals. Residual sprays are an important control method for anthropogenic day-active sylvan mosquitoes such as Aedes albopictus (vector of CHIKV, DENV, and ZIKV) that are difficult to control using ultralow-volume sprays applied only at dusk or dawn when these mosquitoes are not active. In this exploratory study, we analyzed the extent to which ingestion of a sublethal dose of the active ingredient bifenthrin affected vector competence (i.e., infection, dissemination, and transmission) of Ae. albopictus for DENV and ZIKV. Two incubation periods (IPs; 7 and 14 d) were tested at 28°C for insecticide-fed and sugar-fed mosquitoes. We show that mosquitoes that were fed bifenthrin (0.128 µg/mL) mixed with sucrose solution exhibited significantly lower DENV infection rates and body titers after a 14-d IP. During the 7-d IP, one mosquito (sugar group) transmitted ZIKV. During the 14-d IP, 100% of mosquitoes showed body and leg ZIKV infections, and one mosquito (sugar+bifenthrin group) transmitted ZIKV. This is a preliminary communication, and more studies will be required to further investigate these findings. We expect the findings of this small-scale study to spur larger-scale investigations of the impacts of insecticides on mechanisms regulating vector competence, and exposure to other active ingredients, and aid in development of new insecticides.